THE SITUATION OF ANTIBIOTIC USE AT THONG NHAT HOSPITAL (Vietnam Journal of Community Medicine, 2022)
Objectives: Surveying the situation of antibiotic use at Thong Nhat Hospital. Subjects and methods: retrospective descriptive study on 158 medical records of patients discharged from hospital from February 20th, 2020 to February 24th, 2020 (5 days) was kept at the medical records store, Department of general planning, Thong Nhat hospital. Results: In the period of 2019-2020, Penicillin group antibiotics combining beta lactamase inhibitors (90.36% in 2019 and 75.29% in 2020) and C3G + C4G group (86.10% in 2019 and 111,35% in 2020) was most commonly used in the hospital. The antibiotics used on patients consisted of 5 groups, of which, the cephalosporin antibiotic group accounted for the highest proportion of 42.52%; Cefotaxim was used the most with 13.39%. The quinolone group accounted for the lowest percentage (10.50%). Most of the treatment regimen was a combination of 2 antibiotics, accounting for 65.19% and the  change the treatment effectiveness and were worse had a lower proportion, 7.59% and 5.06%, respectively. Hospital transfered patients accounted for a low rate of 1.27%. Conclusion: The group of cephalosporin antibiotics was most commonly used. Most of the treatment regimen was a combination of 2 antibiotics and the majority of patients used oral antibiotics. The average duration of treatment was 11.20 ± 4.32 days. Treatment of recovery and relief/reduction accounted for 51.90% and 34.18% respectively.
Keywords: The situation of antibiotics use, Thong Nhat Hospital.